Novel synthesis of in situ CeOx nanoparticles decorated on CoP nanosheets for highly efficient electrocatalytic oxygen evolution. Issue 20 (7th September 2021) - Wu, Xiaoxia; Wei, Jiaxu; Zhang, Tong; Yang, Yuchen; Liu, Qingyi; Yan, Xingbin; Tang, Yu
Abstract : CoP nanosheets decorated by  in-situ CeO x nanoparticles were designed through a novel two-step solvothermal-phosphating strategy, which act as an electrode exhibit excellent electrocatalytic performance toward OER in alkaline condition. Abstract : CeO x as a (co-)catalyst has been proved a promising material toward the oxygen evolution reaction (OER) in water splitting. In this study, a novel two-step method for the synthesis of cerium oxide nanoparticles in-situ generatedon CoP nanosheets toward OER is presented. Interestingly, Ce ions were gradually hydrolyzed and oxidized under the action of alkaline ligand andsolvothermal environment, and eventually existed in the form of CeO x on the 2D Co-MOF nanosheets in the first step. In the followed selective phosphating process, 2D Co-MOF nanosheets act as the template are transformed into CoP nanosheets but CeO x  is still maintained. Optimal CeO x /CoP nanosheets exhibit low OER overpotential, small Tafel slope and robust durability. Furthermore, in situ electrochemical Raman spectroscopy demonstrates the transformation of the active catalytic species during the oxidation process. This in situ generation of a cocatalyst and selective phosphidation strategy provides some guidelines for the designing of highly efficient catalysts for OER and even other explorations.